Programas de compliance anticorrupção no contexto da Lei 12.846/13: elementos e estudo de caso - Xavier, Christiano Pires Guerra (2015)
Due to the phenomenon of globalization, there has been an increase in the volume of trade among countries, as well as the concentration of economic power of business organizations. This growth in trade and hence in the amount of money involved in it, created a more favorable environment for corruption. Since corruption harms the global economic order and the democratic system, the International Community has demanded an increase in the State intervention system to fight corruption, mainly from the 1990s. The fight against corruption happened through the commitments made by countries that have signed conventions related to it. The present study has addressed the negative effects of corruption on the Brazilian economy and its society, and the international instruments that have been adopted by the country in an attempt to decrease corruption levels. This article still mentions the Brazilian legal system to fight corruption and the aspects of Law No. 12,846 / 13, known as the anticorruption law. An important aspect of the study was to examine the possibility of reducing the sanctions brought by the Law No. 12,846 / 13, according to the 'mechanisms and internal integrity procedures, audit and incentive to report irregularities and the effective implementation of the codes of ethics and conduct', in order words 'Compliance programs'. It was sought to examine the legal implications of the adoption of anti-corruption Compliance programs, and which of its elements can be considered an effective program based on international standards, and if these elements can be considered efficient and in which extent it can fight corruption. Finally, a search in the company Localiza Rent a Car S/A was carried out, a car rental agency company, in order to check which elements are included in its program, and if there are elements considered as minimum and essential taken from national and international references.